Analysis of Interactive Media Needs Based on Scratch in the Subject “Traditions and Culture of Society” for Fourth Grade Students in Kragan District - Nikmah Layarani; Nur Fajrie; Fina Fakhriyah (JELCre - Journal of Education and Learning Creativity, 2025)
This study aims to analyze the needs of interactive media based on Scratch for teaching the "Traditions and Cultures of Society" material to fourth-grade students in the Kragan District. Using a qualitative research approach, this study gathers data through direct observations, interviews with teachers, and questionnaires distributed to students. The findings show that students exhibited significant interest and engagement during the learning process, especially when they were given the opportunity to create interactive projects based on their local traditions and cultures using Scratch. Furthermore, students demonstrated increased creativity, problem-solving abilities, and collaborative skills during the activities. The study concludes that Scratch, as an interactive, game-based learning tool, provides an effective medium for teaching cultural and traditional content in a way that is engaging and relevant to students’ lives. The use of Scratch enhances students' understanding of local culture, encourages creativity, and fosters critical thinking skills. This research highlights the potential of Scratch as an educational platform in the elementary school context and encourages further exploration of its use in cultural education, particularly in areas rich in local traditions.